2014
DOI: 10.1016/j.canlet.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The p38 MAPK-regulated PKD1/CREB/Bcl-2 pathway contributes to selenite-induced colorectal cancer cell apoptosis in vitro and in vivo

Abstract: Supranutritional selenite has anti-cancer therapeutic effects in vivo; however, the detailed mechanisms underlying these effects are not clearly understood. Further studies would broaden our understanding of the anti-cancer effects of this compound and provide a theoretical basis for its clinical application. In this study, we primarily found that selenite exposure inhibited phosphorylation of cyclic adenosine monophosphate (cAMP)-response element binding protein (CREB), leading to suppression of Bcl-2 in HCT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…We first examined whether TES affected the MAPK signaling pathways, as these have previously been shown to play an important role in CRC [26, 27]. P38 phosphorylation levels were dramatically elevated in Lenti-TES cells compared with Lenti-NC cells, whereas extracellular signal-regulated kinase (ERK) and Jun N-terminal Kinase (JNK) were not significantly affected (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…We first examined whether TES affected the MAPK signaling pathways, as these have previously been shown to play an important role in CRC [26, 27]. P38 phosphorylation levels were dramatically elevated in Lenti-TES cells compared with Lenti-NC cells, whereas extracellular signal-regulated kinase (ERK) and Jun N-terminal Kinase (JNK) were not significantly affected (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is also implicated in the initiation and progression of many human malignancies [28][29][30] . We observed that MEK2 was expressed highly in glioma cells, and its expression level increased as tumor grade advanced.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that RRM2 behaves as a critical effector which promotes CREB1 induced aggressiveness of CRC cells. In addition to increasing RRM2 expression, CREB1 also performs a role in inhibiting cell apoptosis by activating PKD1/CREB/Bcl-2 pathway in CRC [32]. Coincidently, RRM2 could also increase Bcl-2 protein stability in Head and Neck and Lung Cancers [33].…”
Section: Discussionmentioning
confidence: 99%